Pneumatically actuated deployable tissue distension device for NOTES for colon - Miyasaka, Muneaki (2020)
When performing some surgical tasks inside colon with NOTES technology, colon tissue could block the task space and occlude the endoscopic vision. In order to solve this problem, we developed a pneumatically driven deployable and undeployable structure which can distend collapsing tissue and can be delivered through a 4.5 mm endoscopic channel. The structure is designed to be flexible enough to pass through colon's tortuous pathway. Also, it is designed to hold its shape without continually applying air pressure after deployment. This allows to make use of an endoscopic channel for the other surgical instruments. Besides, due to the compliant nature of the device, it is safe to deploy inside a smaller space than its maximum deployable size. The functionality of the device was verified with an in-vitro experiment. The structure was successfully deployed inside a pig's colon with an inner diameter of 60 mm by applying 3.5 bars of air pressure and created a sufficient task space for surgical operations.